The Dark Side of Social Media as a Threat on Social-Cultural Resilience - Yulia Rahmawati; Maria Puspitasari (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
Progress technology has brought social media that gives convenience for users to interact and communicate with a user others without restricted distance and time though there is side dark to the important use of social media understood. Study this aim identify side dark social media that can become a source threat to endurance social culture. Study this use approach qualitative descriptive. Study this utilize secondary data as ingredients study. Data collection with the use of study documents. Results study show that side social media dark as conflict, cyberbullying, separatism and speech hate is very dangerous and have the potential Becomes threaten endurance social culture because become the wrong tool for inciting and complaining sheep public To use interest politics and economics parties certain until could break the split union. Because that, needed the right way as expected digital literacy could add knowledge public in media socially wise, intelligent, and positive. Besides, in addition, digital literacy is also expected to make the public capable choose Useful information to improve the quality of self and life.